Enhanced Monitoring of the Preterm Infant during Stabilisation in the Delivery Room - Daragh eFinn; Daragh eFinn; G B Boylan; G B Boylan; C A Ryan; C A Ryan; Eugene Michael Dempsey; Eugene Michael Dempsey (Frontiers Media S.A., 2016)
Monitoring of preterm infants in the delivery room remains limited. Current guidelines suggest that pulse oximetry should be available for all preterm infant deliveries, and that if intubated a colormetric carbon dioxide detector should provide verification of correct endotracheal tube placement. These two methods of assessment represent the extent of objective monitoring of the newborn commonly performed in the delivery room. Monitoring non-invasive ventilation effectiveness (either by capnography or respiratory function monitoring), and cerebral oxygenation (near infrared spectroscopy) are becoming more common within research settings. In this article, we will review the different modalities available for cardio-respiratory and neuro-monitoring in the delivery room, and assess the current evidence base on their feasibility, strengths and limitations during preterm stabilisation.